Procedural knowledge in development of scientific thinking in teachers: certain experimental sequences - Sanduleac, Sergiu (CEP USM, 2024)
This paper analyzes the role of procedural knowledge in the development of scientific thinking and the formation of teaching staff. Procedural knowledge involves skills and procedures, i.e., how we perform certain activities or tasks. Procedural knowledge, in essence, is application-level competences that are related to practical skills and ,,know-how” in a particular domain. These types of knowledge are essential for the functioning of scientific thinking in complex problem-solving. The article presents the results of a study conducted on a sample of teachers. The study demonstrates that the development-efficiency of scientific thinking among teachers can be facilitated by the exploration of a specially developed training program, focused on the consolidation of declarative knowledge/ competences at the level of knowledge, the systematic involvement of metacognition and the stimulation of procedural competences development at the level of integration.

Articolul pune în discuție rolul cunoștințelor procedurale în dezvoltarea gândirii științifice și în formarea cadrelor didactice. Cunoștințele procedurale implică abilități și proceduri, adică modalitățile în care realizăm anumite activități sau sarcini. Cunoștințele procedurale, în esență, reprezintă competențele la nivel de aplicare, care sunt legate de aptitudinile practice și know-how-ul într-un anumit domeniu. Aceste tipuri de cunoștințe sunt esențiale pentru funcționarea gândirii științifice în rezolvarea problemelor complexe. În articol sunt prezentate rezultatele unui studiu realizat pe un eșantion de cadre didactice. Studiul demonstrează că dezvoltarea-eficientizarea gândirii științifice la cadrele didactice poate fi facilitată de explorarea unui program formativ special elaborat, axat pe consolidarea cunoștințelor declarative /competențe la nivel de cunoaștere, implicarea sistematică a metacogniției și stimularea dezvoltării competențelor procedurale la nivel de integrare.
Cunoștințele procedurale în dezvoltarea gândirii științifice la cadrele didactice: unele secvențe experimentale
Keywords: procedural knowledge; scientific thinking; teaching staff; development; cunoștințe procedurale; gândire științifică; cadre didactice; dezvoltare